DevOps: Puppet, Docker, and Kubernetes : get hands-on recipes to automate and manage Linux containers with the Docker 1.6 environment and jump-start your Puppet development /: get hands-on recipes to automate and manage Linux containers with the Docker 1.6 environment and jump-start your Puppet development. (2017) - Uphill, Thomas; Arundel, John; Khare, Neependra; Saito, Hideto; Lee, Hui-Chuan Chloe; Hsu, Ke-Jou Carol
No abstract available